FEATURES OF DEFORMATION, DESTRUCTION AND CALCULATION OF DAMAGED BASALT CONCRETE BEAMS REINFORCED WITH CARBON FIBER CLOTH (Collection of scientific works «Modern structures of metal and wood», 2022)
The  article  presents  the  results  of  tests  of  concrete  beams  with  basalt—plastic reinforcement (BFRP). These beams in previous studies were brought to the limit (ULS) state, and then reinforced with carbon fiber webs (CFRP). The established character of deformation, crack development and fracture used in beams with large (a/d=3) and medium (a/d=2) shear spans corresponded to the stress — strain state of almost balanced normal cross section. It was characterized by the achievement in the outer carbon—plastic layer of the strengthening of ultimate deformations and tensile stresses, and in the compressed zone of concrete — closed (in the descending section of the diagram " σ с —ε с  ") stresses and strains. The destruction of beams with small (a/d=1) landslides was accompanied by further opening of previously formed inclined cracks and rupture of closed carbon fiber shirts on the side faces. Reinforcement of normal sections is recommended to be designed for cases of achievement of characteristic  stresses  in  the  stretched  rod  reinforcement  with  the  subsequent  rupture  of  external FAP—FRP reinforcement without destruction of the compressed zone of concrete. The resulting transverse force in the inclined section of the beam consists of the transverse forces perceived by the concrete of the compressed zone above the top of the dangerous inclined crack, composite reinforcement crossed by the crack, clamps or canvas with FAP—FRP. The method of determining the load—bearing capacity of inclined sections of unreinforced concrete  beams  reinforced  with  NCA—FRP  is  described  in  previously  published  works  of  the authors. The bearing capacity of the ULS—supported support sections of beam structures reinforced with FAP—FRP materials should be determined, first of all, by the action of the bending moment on the critical inclined crack.